How to Utilize CAT and mMRC Scores to Assess Symptom Status of Patients with COPD in Clinical Practice? - Esra ERTAN YAZAR; Elif Yelda NIKSARLIOGLU; Burcu YIGITBAS; Mesut BAYRAKTAROGLU (Medeniyet Medical Journal)
Objective: In this study, we aimed to investigate the compatibility of modified Medical Research Council (mMRC) and COPD assessment test (CAT) scores of chronic obstructive pulmonary disease (COPD) patients in terms of evaluation of their symptom status. Methods: The study was planned as a single-center, cross-sectional study. Statistically four separate receiver operating characteristic (ROC) curves of CAT scoring were generated for mMRC scores of 1 to 4. Results: Two hundred twenty eight patients with stable COPD, mean age 64.2+-8.2 and 88.6% male were included. A strong positive correlation was detected between CAT and mMRC (r=0.60, p<0.001). However, it was observed that 32 patients had mMRC<2 but CAT≥10, while 21 patients had CAT<10 but mMRC≥2. Thus, in 53 patients CAT and mMRC scores were not identical in terms of assessed symptom status. According to the ROC analysis, the mMRC scores of 1 to 4 were most compatible with the CAT scores of 10, 10, 15, and 20, respectively. Conclusions: Expanding current data represents that CAT score of 10 could be more compatible with mMRC score of 1. Moreover we think although a high mMRC or CAT score may be sufficient to assign patients to high symptom groups, it is needed to evaluate mMRC and CAT together to assign a patient to a low symptom group. In this way misclassification of the patients with high symptoms due to insufficient symptom evaluation as if they have low symptoms can be prevented.